Consider a sequence of numbers f i such that f n = f n − 1 + f n − 2 for every integer n ≥ 3 . If f 7 = 5 6 , what is
f 1 + f 2 + f 3 + f 4 + f 5 + f 6 + f 7 + f 8 + f 9 + f 1 0 ?
This problem is shared by Muhammad A .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f 1 = a and f 2 = b .
Then we have:
f 3 = a + b
f 4 = a + 2 b
f 5 = 2 a + 3 b
f 6 = 3 a + 5 b
f 7 = 5 a + 8 b
f 8 = 8 a + 1 3 b
f 9 = 1 3 a + 2 1 b
f 1 0 = 2 1 a + 3 4 b
Then:
f 1 + f 2 + f 3 + f 4 + f 5 + f 6 + f 7 + f 8 + f 9 + f 1 0
= 5 5 a + 8 8 b = 1 1 ∗ ( 5 a + 8 b ) = 1 1 ∗ f 7 = 1 1 ∗ 5 6 = 6 1 6
Let f 1 be a , and let f 2 be b . Now, using the recurrence relation:
f 3 = a + b f 4 = a + 2 b f 5 = 2 a + 3 b f 6 = 3 a + 5 b f 7 = 5 a + 8 b f 8 = 8 a + 1 3 b f 9 = 1 3 a + 2 1 b f 1 0 = 2 1 a + 3 4 b Now, we are given f 7 = 5 6 = 5 a + 8 b , and we must find f 1 + f 2 + f 3 + f 4 + f 5 + f 6 + f 7 + f 8 + f 9 + f 1 0 . Adding up our above terms, our sum is equal to 5 5 a + 8 8 b . Finally, 5 5 a + 8 8 b = 1 1 ( 5 a + 8 b ) = 1 1 f 7 = 1 1 ( 5 6 ) = 6 1 6 .
Note that from the recurrence relation, that f 3 = f 1 + f 2 . Similarly, f 4 = f 3 + f 2 = ( f 1 + f 2 ) + f 2 = f 1 + 2 f 2 . One can immediately see that a pattern emerges (easily proven by induction): that if a n is the nth Fibonacci number (and n ≥ 3 ), then f n = a n − 2 f 1 + a n − 1 f 2 .
To prove this via induction, note that the base has already been previously shown. To prove the inductive step, assume that it holds for all integers up to some k . Then we have that f k + 1 = f k − 1 + f k = ( a k − 3 f 1 + a k − 2 f 2 ) + ( a k − 2 f 1 + a k − 1 f 2 ) = f 1 ( a k − 3 + a k − 2 ) + f 2 ( a k − 2 + a k − 1 ) = f 1 a k − 1 + f 2 a k , as desired.
Therefore, we can represent each f i in terms of f 1 and f 2 . Summing up the corresponding values for i = 1 , 2 , … , 1 0 yields that the sum is equivalent to 5 5 f 1 + 8 8 f 2 . However, note that f 7 = a 5 f 1 + a 6 f 2 = 5 f 1 + 8 f 2 = 5 6 . Therefore, we have that the sum is equal to 5 5 f 1 + 8 8 f 2 = 1 1 ( 5 f 1 + 8 f 2 ) = 1 1 f 7 = 1 1 ⋅ 5 6 = 6 1 6 .
suppose: f(1)=a and f(2)=b f(3) =a + b f(4) =a + 2b f(5) =2a + 3b f(6) =3a + 5b f(7) =5a + 8b f(8) =8a + 13b f(9) =13a + 21b f(10) =21a + 34b
Then sum f(1) until f(10) f(1)+f(2)+f(3)+f(4)+f(5)+f(6)+f(7)+f(8)+f(9)+f(10) = 55a+88b =11(5a + 8b) =11(56) =616
f 1 + f 2 + f 3 + f 4 + f 5 + f 6 + f 7 + f 8 + f 9 + f 1 0 = f 1 + f 2 + f 3 + f 4 + f 5 + f 6 + f 7 + f 8 + f 8 + f 9 + f 9 = f 1 + f 2 + f 3 + f 4 + f 5 + f 6 + f 7 + f 7 + f 7 + f 8 + f 8 + f 8 + f 8 = f 3 + f 3 + f 4 + f 5 + f 6 + f 7 + f 7 + f 7 + f 6 + f 7 + f 6 + f 7 + f 6 + f 7 + f 6 + f 7 = f 3 + f 5 + f 5 + f 6 + f 6 + f 6 + f 6 + f 6 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 = f 3 + f 7 + f 7 + f 6 + f 6 + f 6 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 = f 3 + f 6 + f 6 + f 6 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 = f 3 + f 4 + f 5 + f 6 + f 6 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 = f 5 + f 5 + f 6 + f 6 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 = f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 + f 7 = 5 6 + 5 6 + 5 6 + 5 6 + 5 6 + 5 6 + 5 6 + 5 6 + 5 6 + 5 6 + 5 6 = 616
Denote ( x , y ) to be x ∗ f 1 + y ∗ f 2 . Our strategy is to represent f 7 and the required sum.
By brute force, we calculate:
f 1 = ( 1 , 0 )
f 2 = ( 0 , 1 )
f 3 = ( 1 , 1 )
f 4 = ( 1 , 2 )
f 5 = ( 2 , 3 )
f 6 = ( 3 , 5 )
f 7 = ( 5 , 8 )
f 8 = ( 8 , 1 3 )
f 9 = ( 1 3 , 2 1 )
f 1 0 = ( 2 1 , 3 4 )
We can find that f 7 = ( 5 , 8 ) and the sum is ( 5 5 , 8 8 ) = 1 1 ∗ ( 5 , 8 ) = 1 1 ∗ 5 6 = 6 1 6 as desired.
From the sequence, it is seen that the term is the sum of the previous and the previous previous term. This is a familiar sequence known as the fibonacci sequence where the original sequence goes 1,1,2,3,5,8...... Therefore, Let f1 = a Let f2 = b f3 = a +b f4 = a + 2b f5 = 2a + 3b f6 = 3a + 5b f7 = 5a + 8b f8 = 8a + 13b f9 = 13a + 21b
sum of the first 10 terms is 55a + 88b and f7 = 5a + 8b which is 11 times smaller than the sum. Therefore, if f7 = 56, then sum of the first 10 terms will be 56 x 11 = 616
Let f 1 = x and f 2 = y . Then f 7 = 5 x + 8 y = 5 6 . The problem implies that f 1 + f 2 + . . . + f 9 + f 1 0 is constant. So it doesn't matter what x and y are, as long as they satisfy 5 x + 8 y = 5 6 . To make the calculations simpler, we let x = 8 and y = 2 . Calculating f 1 to f 1 0 and adding gives 6 1 6 .
The sequence will be of the form : a , b , ( a + b ) , ( a + 2 b ) , ( 2 a + 3 b ) , ( 3 a + 5 b ) , ( 5 a + 8 b ) , ( 8 a + 1 2 b ) , ( 1 3 a + 2 0 b ) , ( 2 1 a + 3 2 b ) The seventh term in this sequence is : 5 a + 8 b Therefore 5 a + 8 b = 5 6 The only solutions ∈ Z + is ( 0 , 7 ) , ( 8 , 2 ) So a = 0 or 8 and b = 7 or 2 So in all there are two series possible. Substituting any solution set and summing the we get the sum as 6 1 6
Actually considering negative solutions as well, we get the same sum.
Observe that
f 7 = f 6 + f 5 = 2 f 5 + f 4 = 3 f 4 + 2 f 3 = 5 f 3 + 3 f 2 = 8 f 2 + 5 f 1 .
Then
i = 1 ∑ 1 0 f i = = = = f 1 + f 2 + ( f 1 + f 2 ) + ( f 1 + 2 f 2 ) + ( 2 f 1 + 3 f 2 ) + ( 3 f 1 + 5 f 2 ) + ( 5 f 1 + 8 f 2 ) + ( 8 f 1 + 1 3 f 2 ) + ( 1 3 f 1 + 2 1 f 2 ) + ( 2 1 f 1 + 3 4 f 2 ) 5 5 f 1 + 8 8 f 2 1 1 f 7 6 1 6 .
By simplifing we can say that f7=56=5f0+8f1
Which is just correct for f0=0 &f1=7
Or f0=10 &f1=2( neglected because fn+1>fn)
So 0,7,7,14,21,.....etc
I'm gonna right my answer in terms of rate of change. Look:
f
n
=
f
n
−
1
+
f
n
−
2
. I'm just gonna do this:
f
n
−
1
f
n
=
f
n
−
2
f
n
−
1
.
f
n
−
2
=
f
n
−
f
n
−
1
⟹
f
n
−
1
f
n
=
(
f
n
−
f
n
−
1
)
f
n
−
1
.
This will give me:
f
n
−
1
f
n
=
1
+
f
n
f
n
−
1
.
I will call
n
−
1
f
n
as
ϕ
. This emply:
ϕ
=
1
+
ϕ
1
. Multiply the terms by
ϕ
:
ϕ
2
−
ϕ
−
1
=
0
⟹
ϕ
=
2
1
±
5
. Since the sequence is made of consecutively sums, just consider
ϕ
=
2
1
+
5
, which is approximately
1
.
6
1
8
.
Back to f 7 = 5 6 . 1 . 6 1 8 5 6 = 3 4 . 6 4 1 . I'm gonna work with two integer answer for f 6 : 3 5 or 3 4 . Both will work. The rest of the job it's just elementary algebra with subtraction. Both answer will give this:
0
,
7
,
7
,
1
4
,
2
1
,
3
5
,
5
6
,
9
1
,
1
4
7
,
2
3
8
. Sum equal to
6
1
6
;
8
,
2
,
1
0
,
1
2
,
2
2
,
3
4
,
5
6
,
9
0
,
1
4
6
,
2
3
6
. Sum equal to
6
1
6
.
As explained below, this solution is incorrect as it makes the assumption that f n − 1 f n = f n − 2 f n − 1 , which is only true as a rough approximation.
Can you explain the second equation? How did you get f n − 1 f n = f n − 2 f n − 1 ?
Log in to reply
Well, the sequence goes as f n = f n − 1 + f n − 2 :
. . . . . , f n − 2 , f n − 1 , f n , . . . . . . . . I'm looking for the rate of change of the values, and I'm claiming that f n − 1 f n should be equal to f n − 2 f n − 1 . It's like: a 4 a 5 = a 3 a 4 = a 2 a 3 = a 1 a 2 .
After that, I'm gonna use the value of ϕ to approximate f 6 .
Log in to reply
The claim is not true. They are close enough, but are not equal. For example, if f 1 = 1 , f 2 = 1 then we have f 3 = f 2 + f 1 = 2 . And we do not have the "constant rate of change of (relative) values" since 1 1 = 1 2 .
Log in to reply
@Calvin Lin – Yes. It doesn't work for the first numbers, and rarely it's true for two numbers, but it's useful for approximations, which I should made it clear and used the ≈ sign. My mistake. In fact, something not secret but well known about sequences with: f n = f n − 1 + f n − 2 , is that you can pick any sequence with this property and after pick two consecutive numbers which are not in the beginning (the further away, better) and divide them (bigger one over the smaller one), an approximation of the golden ration will appears. Not just the Fibonacci sequence, as I thought. Anyway, a lot to learn.
Log in to reply
@Marco Antonio – Your claim holds for most such sequences. However, one sequence where it fails is f i = ϕ − i . In this case, the ratio is ϕ − 1 .
The reason for this is that the general solution to the recurrence relation f n = f n − 1 + f n + 2 is of the form f n = A ϕ n + B ϕ − n . If A = 0 , then for large enough n , we have ∣ A ϕ n ∣ > > ∣ B ϕ − n ∣ , in which case the ratio of terms tends towards ϕ .
Problem Loading...
Note Loading...
Set Loading...
Using the recurrence relation given, all terms in the desired sum can be written in terms of f 7 and f 8 (or, really, any two consecutive terms). The easier terms to find are
f 9 = f 7 + f 8
and
f 1 0 = f 8 + f 9 = f 8 + ( f 7 + f 8 ) = f 7 + 2 f 8 .
Then, working "backwards," we can use the fact that f n = f n + 2 − f n + 1 for all integers n ≥ 1 :
f 6 f 5 f 4 f 3 f 2 f 1 = f 8 − f 7 = f 7 − f 6 = f 7 − ( f 8 − f 7 ) = 2 f 7 − f 8 = f 6 − f 5 = ( f 8 − f 7 ) − ( 2 f 7 − f 8 ) = − 3 f 7 + 2 f 8 = f 5 − f 4 = ( 2 f 7 − f 8 ) − ( − 3 f 7 + 2 f 8 ) = 5 f 7 − 3 f 8 = f 4 − f 3 = ( − 3 f 7 + 2 f 8 ) − ( 5 f 7 − 3 f 8 ) = − 8 f 7 + 5 f 8 = f 3 − f 2 = ( 5 f 7 − 3 f 8 ) − ( − 8 f 7 + 5 f 8 ) = 1 3 f 7 − 8 f 8
So the sum of the ten terms now becomes
= = = ( 1 3 − 8 + 5 − 3 + 2 − 1 + 1 + 0 + 1 + 1 ) f 7 + ( − 8 + 5 − 3 + 2 − 1 + 1 + 0 + 1 + 1 + 2 ) f 8 1 1 f 7 + 0 f 8 1 1 ( 5 6 ) 6 1 6 .